(untitled) (Indian Journal of Animal Production and Management, 2018)
Present study was conducted to examine the effect of different seasons on anti-oxidative enzymatic status and lipid peroxidation of Murrah buffalo semen. Semen of six breeding Murrah bulls was collected twice a week using AV method for one complete year. A total of 144 semen samples were collected in entire experiment. Seminal plasma was separated and stored at –20°C. Malondialdehyde (MDA) concentration was estimated in fresh semen samples, while total anti-oxidant capacity (TAC) and superoxide dismutase (SOD) activities were determined in seminal plasma by spectrophotometry. The MDA concentration was found to be significantly (p < 0.01) different in different seasons. Minimum concentration of MDA was observed during winter season. Concentration of TAC was significantly (p<0.01) lower in spring and summer season as compared to autumn and winter season, however there was no significant difference in concentration of SOD in different seasons. In conclusion, better anti-oxidant status and lower concentration of MDA was observed in autumn and winter season compared to spring and summer season.